PRINCIPLES OF ISLAMIC LAW IN CRIMINAL LAW REFORM IN INDONESIA - Gunawan Widjaja; Adrian Bima Putra (Adisam Publisher, 2025)
This article discusses the application of Islamic Law principles in criminal law reform in Indonesia, focusing on efforts to integrate Islamic norms into the pluralistic national legal system. Using the literature research method, it explores the principles of justice ('adl), balance (tawazun), public good (maslahah), and crime prevention (saddu al- dhara'i) as the foundation for criminal law reform. The results show that despite the challenges in harmonising Islamic law with secular national law, the application of these principles can enrich the Indonesian criminal law system with strong moral and ethical values. In addition, wise and comprehensive integration can optimise the effectiveness of law enforcement and improve the sense of justice in society. This study recommends the need for continuous dialogue between stakeholders to reach consensus and ensure that the resulting laws are inclusive and adaptive to the diversity of Indonesian society. In the long run, criminal law reform that considers the principles of Islamic Law has the potential to strengthen the foundation of national law and improve social welfare.